Implementation of Triple Transposition Vegenere Cipher Algorithm and Cipher Block Chaining for Encoding Text - Fitarius Humendru; Taronisokhi Zebua (The IJICS (International Journal of Informatics and Computer Science), 2018)
Security of confidential text data and personal is very important so that the data is not misused by other parties. Many cryptographic algorithms can be used to secure data to keep the originality of confidential data. This study describes the use of triple transposition vegenere cipher algorithm which is combined with cipher block chaining mode for encoding text data with the aim to optimizing randomize of ciphers generated so that the security of confidential of data text is more optimal